Image analysis applied to morphological properties in wheat and oat cookies - Verdú-Amat, Samuel; Granados-Nevárez, María del Carmen; Heredia-Sandoval, Nina Gisella; Islas-Rubio, Alma Rosa; Vásquez-Lara, Francisco (Revista Mexicana de Ciencias Agrícolas, 2025)
The present study was conducted at the Center for Research in Food and Development in 2024. Image analysis is an essential tool that can be used in food process control. This study aimed to analyze, using imaging techniques, the morphological properties of cookies made with wheat and oats in different percentages and their relationship with cookie firmness. The texture profile of the dough obtained from the different formulations, and the weight, diameter, height, and firmness of the cookies were determined. A morphological characterization of the cookies was carried out by means of image analysis. These measurements focused on the overall color of the surface, as well as the characteristics of the surface and internal texture of the cookies through the analysis of the crumb. The results showed decreased firmness (151.96 N to 103.17 N) as the percentage of substitution increased, a similar behavior was observed in the weight and height of the cookie, whereas the diameter was not affected. Regarding the image analysis, greater cracking of the cookie surface was observed as the percentage of substitution increased. Color changes were observed in the crumb towards lighter areas, indicating a decrease in bubbles in the cookie crumb. Image analysis can be an important alternative to determine the quality of a finished product, in this case, a cookie.
Keywords: cookie firmness; image segmentation; surface cracks